ifas-1 is upregulated by fungal infection in a GPA-12 and STA-2-independent manner in the Caenorhabditis elegans epidermis - Omi, Shizue (MicroPubl Biol, 2021)
Skin infection with the fungus Drechmeria coniospora leads to a transcriptional response in the worm epidermis. This involves an increased expression of a group of antimicrobial peptide (AMP) genes including those in the nlp-29 and cnc-2 clusters. The major pathways leading to the expression of these AMP genes have been well characterized and converge on the STAT transcription factor STA-2. We reported previously that expression in the epidermis of a constitutively active (gain of function, gf) form of the Gα protein GPA-12 (GPA-12gf) recapitulates much of the response to infection. To reveal parallel pathways activated by infection, we focus here on an effector gene that is not induced by GPA-12gf. This gene, ifas-1, encodes a protein with a fascin domain, associated with actin binding. Its induction upon fungal infection does not require sta-2. A transcriptional reporter revealed induction in the epidermis of ifas-1 by infection and wounding. Thus, ifas-1 represents part of a previously unexplored aspect of the innate immune response to infection.